Dynamic mechanical relaxations of electrospun poly(acrylonitrile-co-methyl acrylate) nanofibrous yarn. Issue 18 (November 2017) - Hosseini, Seyed Abdolkarim; Pan, Ning; Ko, Frank
The phase structure and dynamic mechanical properties of poly(acrylonitrile-co-methyl acrylate) (P(AN-co-MA)) nanofibers collected in the form of twisted yarn via the two-nozzle conjugated electrospinning method were investigated to study the effects of solution concentration and take-up velocity on the relaxation behavior of nanofibers yarn. The wide-angle X-ray diffraction analyses of P(AN-co-MA) nanofibers show a two-phase structure of nanofibers consisting of crystalline and amorphous phases and polymorphic transition from hexagonal to orthorhombic. Heating P(AN-co-MA) nanofibers at over the glass transition temperature led to an increased degree of both crystallinity and crystallite size with no polymorphic change. Three transitions (tan δ peaks) were observed in nanofibrous yarn prepared at different spinning dope concentrations and take-up speeds, except for the specimen prepared at a concentration of 14 wt% and collecting speed of 8 cm/min, wherein no α transition was observed due to improved molecular orientation. The temperature dependence of the dynamic Young's modulus of nanofibrous yarn at different spinning dope concentrations was mainly affected by the diameter of the nanofiber as the morphological property and molecular orientation. Take-up speed was found to affect the γ and α transitions more than the β transition. Moreover, the maximum storage modulus was obtained at a take-up speed of 8 cm/min at all over recorded temperatures.